2017
DOI: 10.1136/heartjnl-2016-310591
|View full text |Cite
|
Sign up to set email alerts
|

Long-term (8–10 years) outcomes after biodegradable polymer-coated biolimus-eluting stent implantation

Abstract: The long-term clinical outcomes after BP-BES implantation were favourable, although angiographic late progression of luminal narrowing did not reach a plateau. The incidence of ST remained notably low, whereas that of major bleeding gradually increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
(20 reference statements)
0
0
2
Order By: Relevance
“…Above all, these results demonstrated that the XIENCE PRIME EECSS has good safety in Chinese patients. Moreover, the incidence of new lesion revascularization was nearly double that of TLR, similarly to the results of a long-term observational study in Japan [18] but inconsistent with Stone et al's conclusion that the incidence of subsequent cardiovascular events is almost equal for culprit and non-culprit lesions [19], possibly because some patients with poly-vascular disease and diabetes were enrolled in the study. In addition, the cumulative rate of major bleeding events increased progressively and eventually reached a relatively low level of 4.4% at 5 years.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Above all, these results demonstrated that the XIENCE PRIME EECSS has good safety in Chinese patients. Moreover, the incidence of new lesion revascularization was nearly double that of TLR, similarly to the results of a long-term observational study in Japan [18] but inconsistent with Stone et al's conclusion that the incidence of subsequent cardiovascular events is almost equal for culprit and non-culprit lesions [19], possibly because some patients with poly-vascular disease and diabetes were enrolled in the study. In addition, the cumulative rate of major bleeding events increased progressively and eventually reached a relatively low level of 4.4% at 5 years.…”
Section: Discussioncontrasting
confidence: 58%
“…Moreover, 3.3% of patients had any MI at 5 years, a higher percentage than that in the Japanese Co-Cr EES study, whereas cardiac death was 2.2% lower than that in the Co-Cr EES (3.8%). Furthermore, other clinical endpoints including any TLR (6.7%) were also lower than observed in previous clinical research on biodegradable polymer-coated biolimus-eluting stents (16.3%) [18] and Co-Cr EES (7.2%) [14] in Japan. Above all, these results demonstrated that the XIENCE PRIME EECSS has good safety in Chinese patients.…”
Section: Discussioncontrasting
confidence: 56%